Intercalators promote the binding of RecA protein to double-stranded DNA. - Thresher, R J (1990)
Ethidium bromide, acridine orange, 4'-(9-acridinylamino)methanesulfon-o-anisidide (o-AMSA), and m-AMSA induce the rapid binding of RecA protein to double-stranded (ds) DNA. The filaments formed appear to retain the drug and are 12.8 nm in diameter with an 8.0-nm pitch. Two classes of drugs have been distinguished: (i) those that bind to RecA protein and induce assembly at low relative concentrations (e.g., ethidium bromide) and (ii) those that do not appear to interact directly with RecA protein and must be present at relatively high drug concentrations to stimulate assembly (e.g., m-AMSA). Ethidium bromide, acridine orange, and quinacrine inhibit RecA protein binding to single-stranded DNA. Addition of ATP to the drug-induced filaments causes the protein to rapidly dissociate from dsDNA, and protein binding to dsDNA diminishes upon extended exposure to room light. We suggest that the structure of the drug-induced filaments may be more typical of the complex that initiates RecA protein assembly along DNA rather than the product of extensive polymerization as induced by adenosine 5'-[gamma-thio]triphosphate.